THE CONTROLLING NUTRITIONAL STATUS (CONUT) SCORE AS NUTRITIONAL SCREENING TOOL AND PREDICTOR OF CLINICAL OUTCOMES IN STROKE - Gunarto, Untung (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Stroke is one of the leading causes of death worldwide and causes a high financial burden. Malnutrition in stroke patients is associated with worse clinical outcomes. However, until now there is no universally agreed gold standard for establishing a diagnosis of malnutrition. The Controlling Nutritional Status (CONUT) score has been reported to have good sensitivity and specificity in detecting malnutrition in hospitals. In addition, the CONUT score has also been shown to have good ability in predicting clinical outcomes of stroke patients. Implementing CONUT Score in clinical practice may provide management consideration.